Lig3-dependent rescue of mouse viability and DNA double-strand break repair by catalytically inactive Lig4 - Medina-Suárez, David; Han, Li; O’Reilly, Sandra; Liu, Jiali; Wei, Chao; Brenière, Manon; Goff, Noah J; Chen, Chen; Modesti, Mauro; Meek, Katheryn; Harrington, Bonnie; Yu, Kefei (Nucleic acids research, 2024)
Abstract Recent studies have revealed a structural role for DNA ligase 4 (Lig4) in the maintenance of a repair complex during non-homologous end joining (NHEJ) of DNA double-strand breaks. In cultured cell lines, catalytically inactive Lig4 can partially alleviate the severe DNA repair phenotypes observed in cells lacking Lig4. To study the structural role of Lig4 in vivo, a mouse strain harboring a point mutation to Lig4’s catalytic site was generated. In contrast to the ablation of Lig4, catalytically inactive Lig4 mice are born alive. These mice display marked growth retardation and have clear deficits in lymphocyte development. We considered that the milder phenotype results from inactive Lig4 help to recruit another ligase to the repair complex. We next generated a mouse strain deficient for nuclear Lig3. Nuclear Lig3-deficient mice are moderately smaller and have elevated incidences of cerebral ventricle dilation but otherwise appear normal. Strikingly, in experiments crossing these two strains, mice lacking nuclear Lig3 and expressing inactive Lig4 were not obtained. Timed mating revealed that fetuses harboring both mutations underwent resorption, establishing an embryonic lethal genetic interaction. These data suggest that Lig3 is recruited to NHEJ complexes to facilitate end joining in the presence (but not activity) of Lig4. Graphical Abstract Graphical Abstract